Anticancer Activity of Erianin: Cancer-Specific Target Prediction Based on Network Pharmacology - Yan, Lili; Zhang, Zhen; Liu, Yanfen; Ren, Shuyi; Zhu, Zhiyu; Wei, Lu; Feng, Jiao; Duan, Ting; Sun, Xueni; Xie, Tian; Sui, Xinbing (Frontiers in Molecular Biosciences, 2022)
Erianin is a major bisbenzyl compound extracted from Dendrobium chrysotoxum Lindl, an important traditional Chinese herb. In recent years, a growing body of evidence have proved the potential therapeutic effects of erianin on various cancers, including hepatoma, melanoma, non-small-cell lung carcinoma, myelogenous leukemia, breast cancer, and osteosarcoma. Specially, the pharmacological activities of erianin, such as antioxidant and anticancer activity, have been frequently demonstrated by plenty of studies. In this study, we firstly conducted a systematic review on reported anticancer activity of erianin. All updated valuable information regarding the underlying action mechanisms of erianin in specific cancer were recorded and summarized in this paper. Most importantly, based on the molecular structure of erianin, its potential molecular targets were analyzed and predicted by means of Swiss Target Prediction online server. In the meantime, the potential therapeutic targets of ten types of cancers in which erianin has been proved to have anticancer effects were also predicted via OMIM database. The overlapping targets may serve as valuable target candidates through which erianin exerts its anticancer activity. The clinical value of those targets were subsequently evaluated by analyzing their prognostic role in specific cancer using Kaplan-Meier Plotter and GEPIA. To better assess and verify the binding ability of erianin with its potential targets, molecular flexible docking was performed using Discovery studio (DS). The valuable targets obtained from the above analysis and verification were further mapped to KEGG pathway using DAVID to explore the possible signaling pathways disturbed / regulated by erianin. Furthermore, the in silico prediction of ADMET properties of erianin were also performed and provided in this paper. Overall, in this study, we aimed at (a) collecting all experiments-based important information regarding the anticancer effect and pharmacological mechanism of erianin, (b) providing the predicted therapeutic targets and signaling pathways that erianin might act on in cancers , and specially, (c) providing in silico ADMET properties of erianin.